Excellence in public speaking - Sherwyn P Morreale (Harcourt Brace College, 1998)
The book teaches public speaking skills: learn strategies for addressing culturally diverse audiences; transform anxiety into excitement; the book also guides students through a careful examination of the individual rights, social responsibilities, and the ethical obligations of contemporary public speakers